Assessing the Impact of HIV Preexposure Prophylaxis Scale-Up on Gonorrhea Incidence Among Gay and Bisexual Men in Sydney: A Mathematical Modeling Study. Issue 8 (24th August 2022) - Walker, Michael L.; Stiasny, David; Guy, Rebecca J.; Law, Matthew G.; Holt, Martin; Mao, Limin; Donovan, Basil; Grulich, Andrew E.; Gray, Richard T.; Regan, David G.
Abstract : Our study indicates that quarterly sexually transmissible infection testing of preexposure prophylaxis users could offset increases in gonorrhea incidence that may otherwise occur because of an increase in high-risk sexual behavior. Abstract : Background: The rollout of preexposure prophylaxis (PrEP) for HIV prevention among gay and bisexual men (GBM) is associated with increases in condomless anal intercourse, potentially increasing the incidence of other sexually transmissible infections (STIs). Methods: We developed an individual-based mathematical model to simulate the transmission of Neisseria gonorrhoeae among GBM in Sydney, accounting for changes in sexual practices, STI testing, and PrEP use. We calibrated and validated the model using reported incidence rates for HIV-positive and HIV-negative GBM from 2010 to 2019. Scenarios were run with varying PrEP uptake, PrEP-related STI testing, and PrEP-related sexual behavior and testing intervals up to 2030 to assess the impact of PrEP use on gonorrhea incidence. Results: Preexposure prophylaxis uptake and associated 3-monthly STI testing from 2015 onward resulted in a predicted increase from 20 to 37 N. gonorrhoeae infections per 100 person-years among HIV-negative GBM by the end of 2020. This is lower than the counterfactual predictions of 45 per 100 person-years if PrEP were not scaled up and 48 per 100 person-years with nonadherence to 3-monthly STI testing. Increasing the time between STI tests for PrEP users by 1 month from 2018 results in the incidence rate among HIV-negative GBM increasing by 8% by 2030. If PrEP coverage doubles from 24% to 53%, incidence among HIV-negative GBM declines by 25% by 2030. Conclusions: Behavior change due to widespread PrEP use may lead to significant increases in gonorrhea incidence in GBM, but the recommended quarterly STI testing recommended for PrEP users should reduce incidence by 18% by 2030.